PENDAMPINGAN PEMBUATAN ALAT PERAGA BOLUNDARSI UNTUK MENINGKATKAN PEMAHAMAN MATERI BANGUN RUANG BOLA DI MTSN 4 CIREBON - Izzati, Nurma; Hasanah, Lely; Syifani, Alya; Anika, Anika (LP2M Universitas Ibrahimy, 2025)
This community service activity aimed to support the improvement of mathematics learning quality at MTsN 4 Cirebon by assisting teachers in developing innovative teaching aids. The urgency of this program lies in the abstract nature of spherical geometry, which makes it difficult for students to grasp elements such as radius, diameter, center point, surface area, and volume when explained only verbally. At the same time, teachers are not yet accustomed to independently creating or using teaching aids. The specific goal of this activity was to introduce and guide the use of the “Bolundarsi” teaching aid as a visual and manipulative medium for learning spheres. The method employed was Participatory Action Research (PAR) through socialization, workshops, and classroom mentoring, with data collected via interviews, questionnaires, and observations. The results showed improved teacher skills, high participation, and enhanced student understanding and engagement. Teachers and students responded positively, indicating that Bolundarsi makes learning more interactive and supports a more concrete understanding of spherical concepts.